Ilmu Kimia Tanaman Lauraceae Indonesia: III*. Isolasi Aktinodafnin dan Boldin dari Litsea glutinosa - Sjamsul Arifin Achmad; Euis Holisotan Hakim; Lukman Makmur; Helmi Rizal; Adel Zamri (Journal of Mathematical and Fundamental Sciences, 1990)
Aktinodafnin (I) dan boldin (lI), dua senyawa alkaloid dari jenis benzilisokuinolin, telah dipisahkan dari kulit akar tanaman Litsea glutinosa (Lour) C.B. Robinson var. littoralis Bl., suatu varitas yang belum pernah diselidiki peneliti lain. Struktur kedua alkaloid ini telah ditetapkan dengan cara-cara spektroskopi. Penemuan ini melanjutkan penemuan kami sebelumnya tentang suatu alkaloid fenantren baru, yang dinamai itebein, dari spesies tanaman yang sama. Two benzylisoquinoline alkaloids, actinodaphnine (I) and boldine (II), have been isolated from the root bark of Litsea glutinosa (Lour) C.B. Robinson var. littoralis Bl., a variety which has not yet been investigated by other workers. The chemical structures of both alkaloids have been determined by spectroscopic methods. This is to follow-up our previous work on the isolation of a new phenanthrene alkaloid, named itebeine, from the same plant species.